2020
DOI: 10.3389/fpsyt.2020.00321
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Differences Between Sibling Relationships in Schizophrenia and Nonclinical Sibling Relationships

Abstract: Background: Good sibling relationships in adulthood are known to be a protective factor for mental health. The quality of these relationships is influence by the sibship's inherent characteristics (e.g., birth order, number of brothers and sisters, sex composition, age gaps). The present study explored whether these same determinants can help to explain how individuals experience their relationship with a sibling who has been diagnosed with schizophrenia. Method: A total of 374 adults completed the Adult Sibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Four themes were revealed from the interviews with the participants including ambivalent attachment to the mother, feelings of constant fear and worry, a sense of constant care for the mother, and the mother’s cold and emotionless relationship with the child. Plessis et al (2020) studied differences in sibling relationships in schizophrenic patients and found that parents always differentiated between their healthy and sick children in favor of their healthy children, thus inducing negative emotions in the sick child. In another study, Fountoulakis et al (2018) found that the age of the parents affects the formation of the relationship with the child, and an old age leads to ineffective parent-child relationship and the child always seeks constant care of his/her parent and the child feels that he/she is playing the role of a parent for his/her parents instead of a child (Fountoulakis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Four themes were revealed from the interviews with the participants including ambivalent attachment to the mother, feelings of constant fear and worry, a sense of constant care for the mother, and the mother’s cold and emotionless relationship with the child. Plessis et al (2020) studied differences in sibling relationships in schizophrenic patients and found that parents always differentiated between their healthy and sick children in favor of their healthy children, thus inducing negative emotions in the sick child. In another study, Fountoulakis et al (2018) found that the age of the parents affects the formation of the relationship with the child, and an old age leads to ineffective parent-child relationship and the child always seeks constant care of his/her parent and the child feels that he/she is playing the role of a parent for his/her parents instead of a child (Fountoulakis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…EAS experience substantial emotional burden and distress as a result of their experiences with their siblings with schizophrenia, including sorrow, burnout, shame, fear, and feelings of being neglected by their parents (Blasko, 2007). A recent study of EAS found that family conflict and hostility was often fueled by the severity of symptoms and the lack of information that led to faulty conclusions, such as the idea that their sibling could control their behavior and beliefs (Plessis et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quantitative research and the literature exploring the experiences of SOPEP and their relationship are limited (Bowman et al, 2014;Plessis et al, 2020). Psychosis-related symptoms and behaviours observed by SOPEP have been associated with psychological distress for SOPEP and conflict in family relationships (Lively et al, 2004;Plessis et al, 2020). A history of exhibiting physical violence, aggression and suicidal behaviours in individuals with FEP resulted in higher caregiver burden and lower quality of life for siblings (Bowman et al, 2014(Bowman et al, , 2017.…”
Section: Siblings Of People With Experiences Of Psychosis (Sopep)mentioning
confidence: 99%
“…In some cultures, SOPEP may be obligated to provide care for an ‘ ill ’ sibling and socialised to the caretaking role, as well as act as sources of support to their parents (Amaresha et al, 2014; Bowman et al, 2017). Quantitative research and the literature exploring the experiences of SOPEP and their relationship are limited (Bowman et al, 2014; Plessis et al, 2020). Psychosis‐related symptoms and behaviours observed by SOPEP have been associated with psychological distress for SOPEP and conflict in family relationships (Lively et al, 2004; Plessis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%